2019
DOI: 10.1002/pds.4951
|View full text |Cite
|
Sign up to set email alerts
|

A survey of clarithromycin monotherapy and long‐term administration of ethambutol for patients with MAC lung disease in Japan: A retrospective cohort study using the database of health insurance claims

Abstract: Background: The number of patients with nontuberculous mycobacteriosis (NTM) has increased exponentially in recent years. In Japan, approximately 88.8% of patients with NTM suffer from Mycobacterium avium-intracellulare complex (MAC) lung disease. Incidence of MAC lung disease is increasing in particularly among the middle-aged and elderly women owing to a rapid increase in nontuberculous mycobacterial infections.General treatment for MAC lung disease is chemotherapy. The type of chemotherapy recommended by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Importantly, patients treated by Dermatologists with dual-or triple-drug regimens were excluded from the study to screen out possible cases of NTM skin and soft tissue infections. These results (and the results regarding the length of treatment) indicate adherence to the guidelines may not be optimal, a nding that was also observed in previously published studies from the US, Europe and Japan [8, 9,13,14,[21][22][23][24]. One potential explanation is that these regimens were not used for NTM-LD, but rather for M. marinum skin infection or staphylococcal prosthetic joint infections.…”
Section: Discussionsupporting
confidence: 60%
“…Importantly, patients treated by Dermatologists with dual-or triple-drug regimens were excluded from the study to screen out possible cases of NTM skin and soft tissue infections. These results (and the results regarding the length of treatment) indicate adherence to the guidelines may not be optimal, a nding that was also observed in previously published studies from the US, Europe and Japan [8, 9,13,14,[21][22][23][24]. One potential explanation is that these regimens were not used for NTM-LD, but rather for M. marinum skin infection or staphylococcal prosthetic joint infections.…”
Section: Discussionsupporting
confidence: 60%
“…In addition, Kadota et al and Ito et al showed that CLR + EMB treatment regimens without RIF do not increase macrolide resistance [ 57 , 58 ]. In their analysis of Japanese national health insurance receipt data, Iwao et al reported that the percentage of patients who received CLR monotherapy for MAC-PD for more than 3 months was 9.2% [ 59 ]. Morimoto et al reported that among 77 patients with macrolide-resistant MAC-PD, approximately 20% (15 cases) exhibited AMK MIC >32 μg/mL [ 22 ].…”
Section: Drug Resistant Status Of Major Mycobacterial Pathogensmentioning
confidence: 99%